WACANA TUJAQI PADA PROSESI ADAT PERKAWINAN MASYARAKAT SUWAWA PROVINSI GORONTALO - Fatmah AR. Umar (Fakultas Sastra Universitas Negeri Malang, 2011)
The purpose of this researcth are explain scheme, actor, setting, and theme of tujaqi discourse in procession of married culture in Suwawa society Gorontalo Province, in the statge of motolobalango, momanato, and moponika. This Researceh is using qualitative approach. The result of this research are (1) scheme of tujaqi discourse in procession of marrid culture Suwawa sosioty Gorontalo Province is using stef forward (benning, middle, and end), (2) actor that involved in tujaqi discourse in procession of married culture Suwawa sosioty Gorontalo Provinece consist of many components from senior official until masses including children, (3) setting of tujaqi discourse is patterning setting and spontane ous setting, and (general theme of tujaqi discourse in procession of married culture Suwawa sosioty Gorontalo Province is struggle, making sacrifice and confession